Expermental Study to Investigate the Green Concrete Piers of Bridge Using Different Types of Reinforcement (Journal of University of Babylon for Engineering Sciences, 2019)
This paper investigates the behaviour of four concrete piers reinforced with different types of reinforcement. All piers have identical dimensions of 200mm in width, 200mm in height, and 600mm in length with a column cross-section of 200×300mm and 200mm in depth. Various concrete mixes were used among which are the normal concrete (NC) and the green concrete (GC) which use a recycled aggregate of 50% replacement ratio instead of normal aggregate. CFRP bars and GFRP bars are used for reinforcing pier cap at the top two layers .Experimental tests had been carried out to investigate the behaviour in terms of first cracking load, crack width, failure load, and deflection. The test results showed that the value of load failure of the GC pier was less than that for the NC one by 2.41% with an increase in deflection. Furthermore, CFRP and GFRP pier specimens showed opposite behaviour regarding ‎the failure load. It has been found that the ultimate load of CFRP bars increased the ultimate load by 6.9%, while GFRP bars decreased the ultimate load by ‎‎6.7% in comparison to the pier with steel reinforcement.